2021
DOI: 10.1111/ggi.14272
|View full text |Cite
|
Sign up to set email alerts
|

Driving cessation and physical frailty in community‐dwelling older adults: A longitudinal study

Abstract: Physical frailty is a critical health problem that can increase the risk of adverse health outcomes in older adults. Driving cessation has been associated with negative outcomes such as disability. However, the relationship between physical frailty and driving cessation remains unclear. Thus, this study aimed to examine whether driving cessation is associated with physical frailty transition in community-dwelling older adults.Methods: This prospective cohort study was performed in a community setting in Japan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Ishii et al evaluated driving cessation as the exposure and physical frailty transition as the outcome in a cohort of 2,934 older Japanese adults (9). They reported that driving cessation was a risk factor for frailty, as indicated by a 4.6% versus 17.1% difference in the rates for frailty transition (9). Our study is the first to evaluate time-varying frailty as the exposure and driving cessation as the outcome longitudinally.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Ishii et al evaluated driving cessation as the exposure and physical frailty transition as the outcome in a cohort of 2,934 older Japanese adults (9). They reported that driving cessation was a risk factor for frailty, as indicated by a 4.6% versus 17.1% difference in the rates for frailty transition (9). Our study is the first to evaluate time-varying frailty as the exposure and driving cessation as the outcome longitudinally.…”
Section: Introductionmentioning
confidence: 76%
“…Baseline frailty in this cohort has previously been found to be associated with the rate of DC at 1 year HR of 4.2 (95% CI: 1.9-9.1) for pre-frail and HR of 6.1 (95% CI: 1.4-27.3) for frail participants (8). Ishii et al evaluated driving cessation as the exposure and physical frailty transition as the outcome in a cohort of 2,934 older Japanese adults (9). They reported that driving cessation was a risk factor for frailty, as indicated by a 4.6% versus 17.1% difference in the rates for frailty transition (9).…”
Section: Introductionmentioning
confidence: 81%
“…3 For example, previous studies have reported that driving cessation could lead to frailty, disability, and even mortality. [4][5][6] However, the rate of fatal accidents caused by older drivers is considerably higher (8.9 fatal accidents per 100 000 in license holders ≥75 years) than that caused by younger drivers (< 75 years: 3.8). 1 Moreover, the proportion of fatal accidents anticipate potentially dangerous traffic events, and Ball et al 8 indicated that cognitive training that targeted speed-of-processing and reasoning (up to 10 sessions) reduced the rate of at-fault motor vehicle collisions by approximately 50% over a 6-year follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…Not only is driving a car essential for transportation but it also allows older adults to maintain their life‐space mobility, 2 and it can impact their health 3 . For example, previous studies have reported that driving cessation could lead to frailty, disability, and even mortality 4–6 . However, the rate of fatal accidents caused by older drivers is considerably higher (8.9 fatal accidents per 100 000 in license holders ≥75 years) than that caused by younger drivers (< 75 years: 3.8) 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, older adults’ cessation of driving is related to their physical frailty [ 15 ] and affects their level of social isolation [ 16 ], life satisfaction or time spent outside [ 17 ], inactivity and lack of interest [ 18 ], networking with friends [ 19 ], paid work, and volunteer activities [ 20 ]. Some studies have also shown that the factors influencing driving cessation in the elderly depend on personal experience and environment, such as hospitalization [ 21 ], area of residence [ 22 , 23 ], relationship with a partner [ 24 ], and financial situation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%